Fatal Cleistanthus collinus Toxicity: A Case Report and Review of Literature. Issue 5 (16th July 2014) - Das, Siddhartha; Hamide, Abdoul; Mohanty, Manoj K.; Muthusamy, Ravichandran
Abstract Cleistanthus collinus is an extremely toxic plant poison. We report a case of suicidal ingestion of boiled water decoction of C. collinus where the patient presented with abdominal pain and giddiness. There was persistent metabolic acidosis and fluctuation in the level of serum potassium. The ECG changes indicated a probable myocardial injury with conduction abnormality. At autopsy, the viscera were found to be congested. The toxins were detected in the viscera and blood by TLC and HPLC. Cleistanthin A and B, collinusin, and diphyllin are the principal toxic constituents of the plant. Consumption of a boiled decoction of leaves is highly toxic and, medical management of patients is mainly supportive because the molecular mechanisms of toxin action are unknown. In the recent years, C. collinus has created a considerable amount of interest because of its complex metabolites and their cytotoxic activities. Through this study, the authors have tried to highlight different properties pertaining to C. collinus.